Programa de transição para a vida adulta de jovens com deficiência intelectual em ambiente universitário - Lopes, Betania Jacob Stange (Universidade Federal de São Carlos, 2016)
The higher education is increasingly a prerequisite for independence aiming for adulthood of young people today. Researchers have pointed out the importance of participation of young people with intellectual disability (ID) in this level of education so that they have better quality of life as adults. In this context, the general main purpose of this research is to analyze the effects of a Transitional Program for Adult Life in University Environment which aims to provide learning experiences for young people’s lives with ID. In order to make this study effective, it was implemented the Programa Próximos Passos (Next Steps Program), a transitional program for adult life in university environment at a University Center in the Metropolitan Region of Campinas (MRC), State of São Paulo. The study involved: four students with ID (two males and two females), aged between 18 and 26 years; nine teachers of special subjects and eighteen teachers of regular subjects from the University Center; and thirty-two tutors, higher education volunteer students, aged between 18 and 44 years. The study was characterized as experimental research, and, in order to make the aims effective, the following data collect tools were used: Support Intensity Scale (SIS); Field Diary Protocol; Activity Performance Registration Protocol for AB design and Mobile Criterion with Baseline and Interventions; and Social Validity questionnaire, which aimed to analyze the perceptions of teachers and tutors in the degree of satisfaction and importance of the program to increase the independence of the students with ID in higher education. Data were analyzed considering the performance of the participants in the Baseline Steps and Interventions of the experimental study. The results indicated that there was a gradual increase in the process of independence of the students with ID in higher education, with higher performance of activities relating to special subjects (learning throughout the life, employment, activities of daily living and social life) followed by academic subjects. The four students who participated in the program maintained the level of independence in the minimum average expected or above during the interventions performed on special subjects. In regular subjects, three of the four participating students remained at the minimum expected average or above, and only one student had difficulties in academic settings. These aspects were worked by teachers of special and regular subjects along with students with ID, with the help of tutors. Thus, this study showed possibilities for students with ID participate in programs in university environment. Because it is a very little-explored area on the national perspective, it is suggested further research in the area, as well as training programs for teachers and tutors aimed at promoting academic repertoire of students with ID in the university environment.
Transition program to adult life of young people with intellectual disability in the university environment
Keywords: Educação especial; Deficiência intelectual; Ensino superior; Transição para a vida adulta; Planejamento centrado no aluno; Special education; Intellectual disability; Higher education; Transition to adulthood; Learner-centered planning; Experimental design; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO